Penerapan Sistem Vertikultur Sebagai Bentuk Revitalisasi Lingkungan dan Penghijauan di Lahan Sempit Pada Kelurahan Putat Gede Kota Surabaya: Pengabdian - Basakhal Mahalani; Dino Dwi Saputra; Zulfa Malikatul Bulqis; Rozanah Aristawati; Nurul Azizah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The program in Putat Gede Village, Surabaya, focuses on environmental revitalization and greening through vertical farming using recycled materials such as plastic bottles. Activities include creating mini gardens on limited land and public education to promote urban sustainability. The goal is to provide innovative solutions for communities in utilizing limited land, improving air quality, controlling microclimates, supporting biodiversity, and providing social, psychological, and economic benefits such as small-scale food security. Vertical farming has proven effective in increasing green space, saving land, beautifying the environment, and improving family food security. The program's sustainability is expected to motivate communities to maintain productive green environments, increase participation, foster a culture of recycling, and support SDGs number 11 on sustainable cities.